Randomized Quality Improvement Trial of Opting-In Versus Opting-Out to Increase Influenza Vaccination Rates during Pregnancy - Susan H. Wootton; Sean C. Blackwell; George Saade; Pamela D. Berens; Maria Hutchinson; Charles E. Green; Sujatha Sridhar; Kara M. Elam; Jon E. Tyson (Thieme Medical Publishers, Inc., 2018)
Abstract Introduction Despite strong recommendations, only 40.6% of pregnant women attending two prenatal clinics were vaccinated against influenza during the 2009 pandemic. We tested whether an opting-out approach would improve vaccine uptake. Methods We conducted a randomized quality improvement (QI) trial to compare opting-out with conventional opting-in consent for influenza immunization. Women age ≥ 18 years attending the University of Texas Health Science Center at Houston (UTHealth) or UT-Medical Branch (UTMB) prenatal clinics during the 2010-2011 influenza season, were eligible. Results We enrolled 280 women (140 UTHealth, 140 UTMB). Both groups had similar mean age (26.0 ± 5.5 years), mean gestational age (19.4 ± 9.5 weeks), and percent with underlying health conditions (20.7%). Vaccination rates with opting-in and opting-out were similar among all (83 vs. 84%), UTHealth (87 vs. 93%), and UTMB patients (79 vs.76%) (p > 0.05). In subsamples of patients assessed, consent strategy did not significantly affect maternal recall of information provided. Conclusion While prenatal influenza vaccination uptake doubled from the 2009-2010 influenza season, opting-out did not perform better than opting-in, a conclusion opposite that we would have reached had this been a nonconcurrent trial. Vaccination rates dropped posttrial; hence, continued research is needed to increase the prenatal influenza immunizations.